Special oil-proof tear-resistant paper bag for fried chicken as well as preparation method and application of special oil-proof tear-resistant paper bag
By using oil-resistant coatings prepared by modified starch and a variety of other materials, the problems of grease penetration and easy damage of existing fried chicken packaging paper bags have been solved, and efficient oil-proof, tear-resistant and environmentally friendly packaging effects are achieved.
Patent Information
- Application Number
- CN202510158313.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When faced with high-greased foods, existing fried chicken packaging paper bags are prone to oil penetration and packaging easily damaged, and the oil-proof coating has high cost, complex production process or poor environmental protection performance.
Corn starch and potato starch are used as raw materials for oil-proof coatings, and through acid pretreatment, cationic modification and esterification modification, collagen, polysaccharide, sodium alginate, PVA and modified montmorillonite are combined to form an efficient oil-proof coating.
It effectively prevents penetration of oil and fat, maintains the freshness and taste of food, and enhances the tear resistance and mechanical strength of the paper bag, ensuring that it is not damaged during carrying and using, and the material is environmentally friendly, safe and easy to degrade.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of food packaging, and in particular relates to an oil-proof and tear-resistant paper bag specially used for fried chicken, and a preparation method and application thereof. Background Art
[0002] In the modern food packaging industry, especially for the packaging of fried foods such as fried chicken, the choice of packaging materials is crucial. During the packaging process of such foods, special attention should be paid to the penetration of grease and the strength of the packaging materials to ensure the freshness, taste and safety of the food. Although traditional packaging paper bags can meet basic packaging needs to a certain extent, they often have problems such as grease penetration and easy damage to the packaging when facing high-fat foods.
[0003] Grease penetration not only affects the taste and freshness of food, but may also cause the outside of the packaging paper bag to become greasy, causing inconvenience to consumers. In addition, the strength of the packaging paper bag is also a key factor, especially during the process of carrying and eating, the paper bag needs to withstand a certain tearing force to avoid damage and causing the food to scatter.
[0004] There are some oil-proof packaging paper bags on the market, which usually use special coatings or laminating treatments to achieve oil-proof effects. However, these products often have problems such as high costs, complex production processes or poor environmental performance. At the same time, some products sacrifice the tear resistance of paper bags while providing oil-proof performance, making the paper bags easy to break during carrying and use.
[0005] Therefore, it is particularly important to develop a paper bag for fried chicken that has both excellent oil resistance and good tear resistance. This paper bag can not only effectively prevent grease penetration and maintain the freshness and taste of food, but also withstand sufficient tearing force to ensure that it will not be damaged during carrying and use. In addition, considering environmental protection and sustainability, the preparation materials and methods of paper bags should also be as environmentally friendly, safe and easy to degrade as possible. Summary of the invention
[0006] The purpose of the present invention is to provide an oil-proof and tear-resistant paper bag for fried chicken, and a preparation method and application thereof. The oil-proof and tear-resistant paper bag for fried chicken can not only effectively prevent grease penetration and maintain the freshness and taste of food, but also can withstand sufficient tearing force to ensure that it will not be damaged during carrying and use.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: The utility model discloses an oil-proof and tear-resistant paper bag specially used for frying chicken, and the structure thereof comprises paper and an oil-proof coating.
[0008] The raw materials for preparing the oil-proof coating include, by weight, 30-50 parts of modified starch, 10-20 parts of collagen, 3-8 parts of polysaccharide, 2-5 parts of sodium alginate, 5-15 parts of PVA, 1-3 parts of glycerol, 3-8 parts of modified montmorillonite and 690-730 parts of water.
[0009] The preparation method of the modified starch comprises the following steps: A1. Starch pretreatment: After starch and acid are mixed, heat in a water bath at 55-65°C for 1-2 hours, adjust the pH to neutral, rinse with deionized water and filter 2-3 times, and dry to constant weight to obtain pretreated starch; A2. Cationic modification treatment: dissolve the alkali in an ethanol aqueous solution with a mass concentration of 65%-75%, add the pretreated starch, heat to 55-65°C, add the cationic modifier, keep heating at 55-65°C in a water bath for 1-2 hours, adjust the pH to neutral, rinse and filter with anhydrous ethanol and deionized water 2-3 times in turn, and dry to constant weight to obtain the cationic modified starch; A3. Dissolve the cationic modified starch in an ethanol aqueous solution with a mass concentration of 65%-75%, and adjust the system pH to 8-10. After heating to 25-35°C, add the esterification modifier, heat in a water bath at 25-35°C for 1-2h, rinse and filter with anhydrous ethanol and deionized water 2-3 times in turn, and dry to constant weight to obtain the modified starch.
[0010] Preferably, the starch includes one or more of corn starch, potato starch, and sweet potato starch; further preferably, corn starch and potato starch.
[0011] Preferably, the moisture content (by weight) of the corn starch is ≤12%, the protein (by weight) content (by weight) is ≤0.35%, and the passing rate through a 100-mesh sieve is ≥99%.
[0012] Preferably, the moisture content (by weight) of the potato starch is ≤15%, the protein (by weight) content (by weight) is ≤0.15%, and the passing rate through a 100-mesh sieve is ≥99%.
[0013] In some preferred embodiments, the corn starch and potato starch are both purchased from Anhui Xinsheng Biotechnology Co., Ltd.
[0014] Preferably, the mass ratio of the corn starch to the potato starch is 1:(0.5-2); further preferably, it is 1:1.
[0015] Preferably, the acid is one or more of hydrochloric acid, sulfuric acid, acetic acid, and malic acid; more preferably, it is hydrochloric acid.
[0016] Preferably, the mass concentration of the acid is 0.8%-1.2%; further preferably, it is 1%.
[0017] Preferably, the mass ratio of starch to acid is 1:(2-3); further preferably, it is 2:5.
[0018] Preferably, in step A2, the base includes one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate; more preferably, it is sodium hydroxide.
[0019] Preferably, the mass ratio of the alkali to the ethanol aqueous solution with a mass concentration of 65%-75% is 1:(90-110); further preferably, it is 1:100.
[0020] Preferably, the mass ratio of the alkali to the pretreated starch is 1:(30-35); further preferably, it is 1:33.
[0021] Preferably, the cationic modifier comprises chitosan quaternary ammonium salt.
[0022] Preferably, the chitosan quaternary ammonium salt has a substitution degree of 90%, substituted at the 2-amino group, a viscosity of 26-36 cP at room temperature, and a molecular weight of 90,000-110,000.
[0023] In some preferred embodiments, the chitosan quaternary ammonium salt is purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0024] Preferably, the amount of the cationic modifier added is 2%-5% of the mass of the starch.
[0025] Preferably, the mass ratio of the cationic modified starch to the ethanol aqueous solution with a mass concentration of 65%-75% is 1:(2-4); further preferably, it is 1:3.
[0026] Preferably, the esterification modifier includes one or more of vinyl acetate, 2-octenyl succinic anhydride, and acetic anhydride; further preferably, it is 2-octenyl succinic anhydride.
[0027] Preferably, the added amount of the esterification modifier is 5%-10% of the mass of the cationic modified starch.
[0028] The use of corn starch and potato starch as raw materials for oil-proof coatings can improve the oil-proof performance, tear resistance, and adhesion to paper of the oil-proof coating. This may be because the two work synergistically. On the one hand, they can form a more delicate and compact structure in the coating, and the gelatinization rates of the two are different. Potato starch first quickly absorbs water and swells to form a gelatinized structure, and then the gelatinization of corn starch further fills and improves this network structure, making the coating more firm and durable. However, although starch materials have a certain oil resistance and can resist oil penetration, their performance is limited, and their water resistance is poor, their mechanical strength is also low, and they are easy to break. Pre-treating starch with acid first, and then sequentially undergoing cationic and esterification modifications, can improve the hydrophobicity of the oil-proof coating and further improve its oil resistance and mechanical strength. This may be because acid pretreatment, as a preliminary step, not only promotes its water absorption, swelling and gelatinization process by destroying part of the crystalline structure of starch, but also activates the hydroxyl groups in the starch molecules, laying a good foundation for subsequent modification reactions. Next, the cationic properties of chitosan quaternary ammonium salt enable it to tightly bind to starch molecules through electrostatic interaction, which not only enhances the interaction between molecules, but also gives the coating certain antibacterial properties, which helps to extend the shelf life of food. Finally, the esterification modification of 2-octenyl succinic anhydride introduces hydrophobic groups into the starch molecules, significantly improving the hydrophobicity and oil-proof properties of the coating, effectively blocking the penetration of grease. In addition, chitosan quaternary ammonium salt and 2-octenyl succinic anhydride both have good biocompatibility and degradability, are environmentally friendly and non-toxic, and can be used as modifiers in the food field.
[0029] The preparation method of collagen comprises the following steps: adding water to gelatin to adjust the mass fraction of gelatin to 5%-8%, adjusting the pH of the system to 8-10, heating to 50-60°C, adding a gelatin modifier, maintaining the temperature at 50-60°C for reaction for 1-2h, dialyzing with deionized water, concentrating, and freeze-drying to obtain collagen.
[0030] Preferably, the viscosity of the gelatin is ≥15 mm 2 / s, moisture (by weight) ≤14%, ignition residue ≤2%.
[0031] In some preferred embodiments, the gelatin is purchased from Yingxin Laboratory.
[0032] Preferably, the gelatin modifier includes one or more of sodium pyrophosphate and sodium tripolyphosphate; further preferably, sodium pyrophosphate and sodium tripolyphosphate.
[0033] Preferably, the mass ratio of the sodium pyrophosphate to sodium tripolyphosphate is 1:(1-2); further preferably, it is 2:3.
[0034] Preferably, the mass ratio of the gelatin to the gelatin modifier is (14-16):1; further preferably, it is 15:1.
[0035] Modifying gelatin with a specific gelatin modifier can improve the oil resistance of the oil-proof coating while improving its tear resistance. This may be because the two gelatin modifiers have a synergistic effect. On the one hand, by chemically reacting with the phosphate groups and amino acid residues in the gelatin molecules, they not only change the molecular structure of gelatin, but also enhance its surface properties, making the formed coating surface smoother and tighter, effectively reducing the path of oil penetration, thereby significantly improving the oil resistance. On the other hand, the interaction force between the modified gelatin molecules is strengthened, forming a more solid and stable gel network structure. This structural characteristic enables the coating to better disperse and resist tearing force when torn by external force, significantly enhancing the tear resistance. In addition, sodium pyrophosphate, as a pioneer reagent, first reacts with gelatin, creating favorable conditions for the subsequent further modification of sodium tripolyphosphate. The two work synergistically to jointly optimize the performance of the coating, so that it maintains high oil resistance while also showing excellent tear resistance and other mechanical properties.
[0036] Preferably, the polysaccharide includes one or more of chitosan and pullulan; further preferably, chitosan and pullulan.
[0037] Preferably, the mass ratio of chitosan to pullulan is 1:(3-5); further preferably, it is 1:4.
[0038] Preferably, the chitosan has a deacetylation degree of ≥95% and a relative molecular mass of 50,000-60,000.
[0039] Preferably, the molecular weight of the sodium alginate is 30,000, and the M / G ratio is 1:2.
[0040] In some preferred embodiments, the chitosan, pullulan and sodium alginate are all purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0041] Preferably, the alcoholysis degree of the PVA is ≥99%, the viscosity of a PVA aqueous solution with a PVA mass concentration of 4% is 24-32 cP, and the ash weight content is <0.5%.
[0042] In some preferred embodiments, the PVA is purchased from Japan Kuraray, ELVANOL™, T-25.
[0043] The preparation method of the modified montmorillonite comprises the following steps: B1. After the montmorillonite is crushed and passed through a 200-400 mesh sieve, water is added to adjust the mass fraction of the montmorillonite to 3%-5%, the temperature is raised to 75-85°C and stirred evenly, a quaternary ammonium salt aqueous solution is added, and the mixture is reacted at 75-85°C for 8-10 hours, the mixture is separated and the liquid is removed, the solid is filtered 2-3 times, and vacuum dried at 60-70°C to obtain the quaternary ammonium salt modified montmorillonite; B2. After ultrasonically dispersing the quaternary ammonium salt modified montmorillonite in a 75%-85% ethanol aqueous solution for 1-3 hours, a coupling agent is added, and the pH value of the system is adjusted to 8-9. After reacting at 65-75°C for 2-4 hours, the mixture is cooled to room temperature, filtered and separated, and washed with deionized water until neutral. The modified montmorillonite is then vacuum dried at 60-70°C.
[0044] Preferably, the montmorillonite is sodium-montmorillonite, has an ion exchange capacity of 140-150 meq / 100 g, and an aspect ratio of 200-400.
[0045] In some preferred embodiments, the montmorillonite is purchased from Jiangsu Xianfeng Nanomaterial Technology.
[0046] Preferably, the mass fraction of the quaternary ammonium salt in the quaternary ammonium salt aqueous solution is 0.5%-1.5%.
[0047] Preferably, the quaternary ammonium salt comprises chitosan quaternary ammonium salt.
[0048] Preferably, the mass of the quaternary ammonium salt is 8%-12% of the mass of montmorillonite.
[0049] Preferably, the mass ratio of the quaternary ammonium salt-modified montmorillonite to the ethanol aqueous solution with a mass fraction of 75%-85% is 1:(10-20).
[0050] Preferably, the coupling agent includes one or more of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane; further preferably, 3-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0051] Preferably, the mass ratio of the 3-(2,3-epoxypropoxy)propyltrimethoxysilane to γ-aminopropyltriethoxysilane is 1:(0.5-2); more preferably, it is 1:1.
[0052] Preferably, the amount of the coupling agent added is 5% to 10% of the mass of the quaternary ammonium salt-modified montmorillonite.
[0053] Adding modified montmorillonite to the raw materials, first modifying it with chitosan quaternary ammonium salt, and then modifying it with two silane coupling agents for the second time can not only improve the hydrophobicity and oil-proof performance of the oil-proof coating, but also enhance the mechanical strength and tear resistance of the coating. In addition, it can also improve the heat resistance and chemical stability of the coating. This may be because the charge density of montmorillonite is increased by first modifying it with chitosan quaternary ammonium salt, increasing its interlayer spacing and promoting its uniform dispersion in aqueous solution. The addition of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane further strengthens the dispersion stability and gives the montmorillonite coating more excellent hydrophobicity. The epoxy group in 3-(2,3-epoxypropoxy)propyltrimethoxysilane and the amino group in γ-aminopropyltriethoxysilane, with their unique chemical properties, physically entangle or chemically react with the montmorillonite and polymer matrix molecular chains, thereby not only enhancing the interfacial bonding force, but also optimizing the internal structure of the coating, making it more dense and uniform. This structural optimization, coupled with the hydrophobic effect brought by 3-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane, jointly improves the oil resistance, mechanical strength, tear resistance, heat resistance and chemical stability of the oil-proof coating.
[0054] The method for preparing the oil-proof coating comprises the following steps: C1. Prepare modified starch emulsion, collagen aqueous solution, polysaccharide aqueous solution, sodium alginate aqueous solution, PVA aqueous solution and glycerol aqueous solution respectively for later use; C2. After stirring the modified starch emulsion and collagen aqueous solution at 65-75°C and 800-1000r / min for 20-30min, add the PVA aqueous solution, heat it to 85-95°C, stir it at 800-1000r / min for 1-2h, add the glycerol aqueous solution, keep stirring at 85-95°C and 800-1000r / min for 30-40min, cool it to 40-50°C, add the polysaccharide aqueous solution and the sodium alginate aqueous solution, continue stirring at 40-50°C and 800-1000r / min for 20-30min, add the modified montmorillonite, stir it at 40-50°C and 800-1000r / min for 20-30min, and obtain the product.
[0055] Preferably, the method for preparing the modified starch emulsion comprises the following steps: adding water to the modified starch to adjust the mass fraction of the modified starch to 10%-15%, and gelatinizing at 65-75° C. for 15-25 min to obtain the modified starch emulsion.
[0056] Preferably, the mass fraction of collagen in the collagen aqueous solution is 10%-15%.
[0057] Preferably, the mass fraction of polysaccharide in the polysaccharide aqueous solution is 2%-5%.
[0058] Preferably, the mass fraction of sodium alginate in the sodium alginate aqueous solution is 2%-5%.
[0059] Preferably, the mass fraction of PVA in the PVA aqueous solution is 5%-10%.
[0060] Preferably, the mass fraction of glycerol in the glycerol aqueous solution is 28-32%.
[0061] By dissolving ingredients such as collagen, polysaccharides, sodium alginate and PVA in water to prepare an aqueous solution and gelatinizing starch in water, the overall performance of the coating can be improved. This may be because the aqueous solution formed by collagen, polysaccharides, sodium alginate and PVA ensures the uniform dispersion of these ingredients during the preparation process, effectively avoiding agglomeration or precipitation, thereby improving the stability and consistency of the coating. At the same time, the modified starch emulsion not only improves the dispersibility and stability of starch in the coating by modifying the starch and dispersing it in water, but also gives the coating the required adhesion and flexibility.
[0062] The method for preparing the oil-proof and tear-resistant paper bag for fried chicken comprises the following steps: fixing the paper on a coating machine, coating the paper with an oil-proof coating at a coating amount of 2-4 g / m 2 , dry at 55-65℃ for 30-50min, and place at room temperature for 1-2 days to obtain.
[0063] Preferably, the paper is imported kraft paper with a longitudinal tear index of 4.13 mN·m 2 / g, transverse tear index is 3.61mN·m 2 / g.
[0064] In some preferred embodiments, the paper is purchased from Canada Galli.
[0065] The application of the oil-proof and tear-resistant paper bag for fried chicken can be applied to fields such as food packaging.
[0066] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention provides a special oil-proof and tear-resistant paper bag for fried chicken, which can not only effectively prevent grease penetration and maintain the freshness and taste of food, but also withstand sufficient tearing force to ensure that it will not be damaged during carrying and use. In addition, the preparation materials of the paper bag are environmentally friendly, safe and easy to degrade, and are very suitable for use in the food field.
[0067] 2. The present invention uses corn starch and potato starch as raw materials for the oil-proof coating, which can improve the oil-proof performance, tear resistance and adhesion between the oil-proof coating and paper.
[0068] 3. The present invention first pre-treats the starch with acid, and then sequentially undergoes cationic and esterification modifications, which can improve the hydrophobicity of the oil-proof coating and further improve its oil resistance and mechanical strength.
[0069] 4. The present invention uses a specific gelatin modifier to modify gelatin, which can improve the oil resistance of the oil-proof coating while improving its tear resistance.
[0070] 5. The present invention adds modified montmorillonite to the raw materials, first modifies it with chitosan quaternary ammonium salt, and then performs secondary modification with two silane coupling agents. This can not only improve the hydrophobicity and oil-proof performance of the oil-proof coating, but also enhance the mechanical strength and tear resistance of the coating. In addition, it can also improve the heat resistance and chemical stability of the coating.
[0071] 6. The present invention uses specific raw materials to prepare a special oil-proof and tear-resistant paper bag for fried chicken with excellent oil-proof performance and tear resistance and certain heat resistance. The modified starch and collagen work synergistically, and the film-forming and waterproof properties complement each other with the adhesion and toughness, forming a solid foundation for the coating. Polysaccharides and sodium alginate, with their unique functional groups and water-solidity, enhance the barrier and water resistance of the coating, and further block the penetration of grease. The addition of PVA, with its excellent barrier and biodegradability, is intertwined with the above components to construct a dense coating structure. By modifying montmorillonite, not only its defect of easy agglomeration is improved, but also its compatibility with other raw materials is improved. Its nano-level lamellar structure and multiple functionalities improve the tear resistance, mechanical strength, heat resistance and antibacterial properties of the oil-proof coating. These raw materials are evenly dispersed with the help of water, and together form an efficient and synergistic system, so that the oil-proof coating and the paper bag prepared therefrom can not only effectively prevent the penetration of grease, but also have excellent tear resistance and are strong and durable. DETAILED DESCRIPTION
[0072] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0073] The raw materials used in the present invention are all commercially available, specifically: The moisture content (weight) of corn starch is ≤12%, the protein content (weight) of dry basis is ≤0.35%, and the passing rate of 100 mesh sieve is ≥99%; the moisture content (weight) of potato starch is ≤15%, the protein content (weight) of dry basis is ≤0.15%, and the passing rate of 100 mesh sieve is ≥99%; both are purchased from Anhui Xinsheng Biotechnology Co., Ltd.
[0074] The substitution degree of chitosan quaternary ammonium salt is 90%, substituted on the 2-amino group, the viscosity at room temperature is 26-36 cP, the molecular weight is 90000-110000, and it was purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0075] The viscosity of gelatin is ≥15mm 2 / s, moisture (by weight) ≤14%, ignition residue ≤2%, purchased from Yingxin Laboratory.
[0076] The deacetylation degree of chitosan is ≥95%, and the relative molecular weight is 50000-60000; the molecular weight of sodium alginate is 30000, and the M / G ratio is 1:2; chitosan, pullulan and sodium alginate are all purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0077] The alcoholysis degree of PVA is ≥99%, the viscosity of the PVA aqueous solution with a PVA mass concentration of 4% is 24-32 cP, and the ash weight content is <0.5%. It is purchased from Kuraray Japan, ELVANOL™, T-25.
[0078] The montmorillonite is sodium-montmorillonite with an ion exchange capacity of 140-150 meq / 100 g and an aspect ratio of 200-400, purchased from Jiangsu Xianfeng Nanomaterial Technology.
[0079] The paper is imported kraft paper with a longitudinal tear index of 4.13mN·m 2 / g, transverse tear index is 3.61mN·m 2 / g, purchased from Canada Gali.
[0080] Example 1 The present embodiment provides an oil-proof and tear-resistant paper bag for fried chicken, which has a structure of paper and an oil-proof coating.
[0081] The raw materials for preparing the oil-proof coating are, by weight, 40 parts of modified starch, 15 parts of collagen, 5 parts of polysaccharide, 3 parts of sodium alginate, 10 parts of PVA, 2 parts of glycerol, 5 parts of modified montmorillonite, and 715 parts of water.
[0082] The preparation method of the modified starch comprises the following steps: A1. Starch pretreatment: After starch and acid are mixed, they are heated in a water bath at 60°C for 1.5 hours, the pH is adjusted to neutral, and the mixture is rinsed and filtered three times with deionized water, and then dried to constant weight to obtain pretreated starch; A2. Cationic modification treatment: dissolve the alkali in an ethanol aqueous solution with a mass concentration of 70%, add the pretreated starch, heat to 60°C, add the cationic modifier, keep heating at 60°C in a water bath for 1.5 hours, adjust the pH to neutral, rinse and filter with anhydrous ethanol and deionized water for 3 times, and dry to constant weight to obtain the cationic modified starch; A3. Dissolve the cationic modified starch in an ethanol aqueous solution with a mass concentration of 70%, and adjust the pH of the system to 9. After heating to 30°C, add the esterification modifier, heat in a water bath at 30°C for 1.5 hours, rinse and filter with anhydrous ethanol and deionized water three times in sequence, and dry to constant weight to obtain the modified starch.
[0083] The starch is corn starch and potato starch in a mass ratio of 1:1.
[0084] The hydrochloric acid.
[0085] The mass concentration of the acid is 1%.
[0086] The mass ratio of the starch to the acid is 2:5.
[0087] In the step A2, the base is sodium hydroxide.
[0088] The mass ratio of the alkali to the ethanol aqueous solution with a mass concentration of 70% is 1:100.
[0089] The mass ratio of the alkali to the pretreated starch is 1:33.
[0090] The cationic modifier is chitosan quaternary ammonium salt.
[0091] The added amount of the cationic modifier is 3.5% of the mass of starch.
[0092] The mass ratio of the cationic modified starch to the ethanol aqueous solution with a mass concentration of 70% is 1:3.
[0093] The esterification modifier is 2-octenyl succinic anhydride.
[0094] The added amount of the esterification modifier is 8% of the mass of the cationic modified starch.
[0095] The preparation method of collagen comprises the following steps: adding water to gelatin to adjust the mass fraction of gelatin to 6.5%, adjusting the pH of the system to 9, heating to 55° C., adding a gelatin modifier, maintaining the temperature at 55° C. for reaction for 1.5 hours, dialyzing with deionized water, concentrating, and freeze-drying to obtain collagen.
[0096] The gelatin modifiers are sodium pyrophosphate and sodium tripolyphosphate, with a mass ratio of 2:3.
[0097] The mass ratio of the gelatin to the gelatin modifier is 15:1.
[0098] The polysaccharides are chitosan and pullulan, and the mass ratio is 1:4.
[0099] The preparation method of the modified montmorillonite comprises the following steps: B1. After the montmorillonite is crushed and passed through a 300-mesh sieve, water is added to adjust the mass fraction of the montmorillonite to 4%, the temperature is raised to 80°C and stirred evenly, and then a quaternary ammonium salt aqueous solution is added. After reacting at 80°C for 9 hours, the mixture is separated and the liquid is removed. After the solid is filtered 3 times, it is vacuum dried at 65°C to obtain a quaternary ammonium salt-modified montmorillonite; B2. After ultrasonically dispersing the quaternary ammonium salt-modified montmorillonite in an 80% by mass ethanol aqueous solution for 2 hours, a coupling agent was added, and the pH value of the system was adjusted to 8.5. After reacting at 70°C for 3 hours, the mixture was cooled to room temperature, filtered and separated, and washed with deionized water until neutral. The modified montmorillonite was obtained by vacuum drying at 65°C.
[0100] The mass fraction of the quaternary ammonium salt in the quaternary ammonium salt aqueous solution is 1%.
[0101] The quaternary ammonium salt is chitosan quaternary ammonium salt.
[0102] The mass of the quaternary ammonium salt is 10% of the mass of the montmorillonite.
[0103] The mass ratio of the quaternary ammonium salt modified montmorillonite to the ethanol aqueous solution with a mass fraction of 80% is 1:15.
[0104] The coupling agent is 3-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-aminopropyltriethoxysilane, and the mass ratio is 1:1.
[0105] The added amount of the coupling agent is 7.5% of the mass of the quaternary ammonium salt modified montmorillonite.
[0106] The preparation method of the oil-proof coating comprises the following steps: C1. Prepare modified starch emulsion, collagen aqueous solution, polysaccharide aqueous solution, sodium alginate aqueous solution, PVA aqueous solution and glycerol aqueous solution respectively for later use; C2. After stirring the modified starch emulsion and collagen aqueous solution at 70°C and 900 r / min for 25 min, add the PVA aqueous solution, raise the temperature to 90°C, stir at 900 r / min for 1.5 h, add the glycerol aqueous solution, keep stirring at 90°C and 900 r / min for 35 min, cool to 45°C, add the polysaccharide aqueous solution and the sodium alginate aqueous solution, continue stirring at 45°C and 900 r / min for 25 min, add the modified montmorillonite, stir at 45°C and 900 r / min for 25 min, and obtain the product.
[0107] The preparation method of the modified starch emulsion comprises the following steps: adding water to the modified starch to adjust the mass fraction of the modified starch to 12%, and gelatinizing at 70° C. for 50 minutes to obtain the modified starch emulsion.
[0108] The mass fraction of collagen in the collagen aqueous solution is 12%.
[0109] The mass fraction of polysaccharide in the polysaccharide aqueous solution is 4%.
[0110] The mass fraction of sodium alginate in the sodium alginate aqueous solution is 4%.
[0111] The mass fraction of PVA in the PVA aqueous solution is 8%.
[0112] The mass fraction of glycerol in the glycerol aqueous solution is 30%.
[0113] The preparation method of the oil-proof and tear-resistant paper bag for fried chicken comprises the following steps: fixing the paper on a coating machine, coating the paper with an oil-proof coating, and coating the paper with a coating amount of 3 g / m 2 , after drying at 60°C for 40 minutes, place it at room temperature for 2 days to obtain the product.
[0114] Example 2 The difference between this embodiment and embodiment 1 is that the raw materials for preparing the oil-proof coating include, by weight, 45 parts of modified starch, 12 parts of collagen, 5 parts of polysaccharide, 3 parts of sodium alginate, 10 parts of PVA, 2 parts of glycerol, 5 parts of modified montmorillonite, and 730 parts of water.
[0115] Comparative Example 1 The difference between this comparative example and Example 1 is that the raw materials for preparing the oil-proof coating are, by weight, 40 parts of starch, 15 parts of collagen, 5 parts of polysaccharide, 3 parts of sodium alginate, 10 parts of PVA, 2 parts of glycerol, 5 parts of modified montmorillonite, and 715 parts of water.
[0116] Comparative Example 2 The difference between this comparative example and Example 1 is that the raw materials for preparing the oil-proof coating are, by weight, 40 parts of modified starch, 15 parts of collagen, 5 parts of polysaccharide, 3 parts of sodium alginate, 10 parts of PVA, 2 parts of glycerol, 5 parts of montmorillonite, and 715 parts of water.
[0117] Comparative Example 3 The difference between this comparative example and Example 1 is that the raw materials for preparing the oil-proof coating are, by weight, 40 parts of modified starch, 15 parts of collagen, 5 parts of polysaccharide, 3 parts of sodium alginate, 2 parts of glycerol, 5 parts of modified montmorillonite, and 600 parts of water.
[0118] Comparative Example 4 The difference between this comparative example and Example 1 is that the preparation method of the modified starch comprises the following steps: A1. Starch pretreatment: After starch and acid are mixed, they are heated in a water bath at 60°C for 1.5 hours, the pH is adjusted to neutral, and the mixture is rinsed and filtered three times with deionized water, and then dried to constant weight to obtain pretreated starch; A2. Cationic modification treatment: dissolve the alkali in an ethanol aqueous solution with a mass concentration of 70%, then add the pretreated starch, heat to 60°C, add the cationic modifier, keep heating at 60°C in a water bath for 1.5 hours, adjust the pH to neutral, rinse and filter with anhydrous ethanol and deionized water for 3 times, and dry to constant weight to obtain the modified starch.
[0119] Comparative Example 5 The difference between this comparative example and Example 1 is that the collagen is gelatin.
[0120] Comparative Example 6 The difference between this comparative example and Example 1 is that the preparation method of the modified montmorillonite comprises the following steps: pulverizing the montmorillonite through a 300-mesh sieve, adding water to adjust the mass fraction of the montmorillonite to 4%, heating to 80°C and stirring evenly, adding a quaternary ammonium salt aqueous solution, reacting at 80°C for 9 hours, stratifying and removing the liquid, filtering the solid three times, and vacuum drying at 65°C to obtain the modified montmorillonite.
[0121] Comparative Example 7 The difference between this comparative example and Example 1 is that the preparation method of the oil-proof coating comprises the following steps: mixing the raw materials, stirring at 45° C. and 900 r / min for 4 hours to obtain the oil-proof coating.
[0122] Performance Testing The oil resistance level of paper bags is determined according to the specifications of TAPPI 559cm-02. The transverse tear index of paper bags is determined according to GB / T 455.1-1989, in mN·m 2 / g. Add 1mL of 85℃ hot oil to the oil-proof coating surface of the paper bag, wipe off the excess oil after 10 minutes, and observe whether the oil penetrates into the imported kraft paper layer and whether there are dark spots on the paper surface. If not, it means that the paper has qualified hot oil resistance. The results are shown in Table 1.
[0123] According to statistics, the oil-proof and tear-resistant paper bags for fried chicken prepared by Examples 1-2 of the present invention have a high oil-proof grade, a high transverse tear index, and excellent heat oil resistance, and can be used to package fried chicken just out of the pan. Comparative Example 1 did not modify the starch, Comparative Example 2 did not modify the montmorillonite, Comparative Example 3 did not add PVA, Comparative Example 4 did not perform secondary modification on the starch, Comparative Example 5 did not modify the gelatin, Comparative Example 6 did not perform secondary modification on the montmorillonite, and Comparative Example 7 did not configure each raw material into a solution and starch into a gelatinized liquid for use. The prepared paper bag has poor oil resistance, tear resistance, and heat oil resistance. Therefore, the oil-proof and tear-resistant paper bag for fried chicken prepared by the raw materials and methods described in this application can not only effectively prevent oil penetration, maintain the freshness and taste of food, but also withstand sufficient tearing force to ensure that it will not be damaged during carrying and use, and has excellent heat oil resistance, can wrap hot fried chicken, and the preparation materials are environmentally friendly, safe and easy to degrade, which is very suitable for application in the food field.
[0124] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A special oil-proof and tear-resistant paper bag for fried chicken, characterized in that: Its structure includes paper, oil-proof coating; The raw materials for preparing the oil-proof coating include, by weight, 30-50 parts of modified starch, 10-20 parts of collagen, 3-8 parts of polysaccharide, 2-5 parts of sodium alginate, 5-15 parts of PVA, 1-3 parts of glycerol, 3-8 parts of modified montmorillonite, and 690-730 parts of water; The preparation method of the modified starch comprises the following steps: A1. Starch pretreatment: After starch and acid are mixed, heat in a water bath at 55-65°C for 1-2 hours, adjust the pH to neutral, rinse with deionized water and filter 2-3 times, and dry to constant weight to obtain pretreated starch; A2. Cationic modification treatment: dissolve the alkali in an ethanol aqueous solution with a mass concentration of 65%-75%, add the pretreated starch, heat to 55-65°C, add the cationic modifier, keep heating at 55-65°C in a water bath for 1-2 hours, adjust the pH to neutral, rinse and filter with anhydrous ethanol and deionized water 2-3 times in turn, and dry to constant weight to obtain the cationic modified starch; A3. Dissolve the cationic modified starch in an ethanol aqueous solution with a mass concentration of 65%-75%, and adjust the system pH to 8-10. After heating to 25-35°C, add the esterification modifier, heat in a water bath at 25-35°C for 1-2h, rinse and filter with anhydrous ethanol and deionized water 2-3 times in turn, and dry to constant weight to obtain the modified starch.
2. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The starch includes one or more of corn starch, potato starch and sweet potato starch.
3. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The cationic modifier includes chitosan quaternary ammonium salt.
4. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The esterification modifier includes one or more of vinyl acetate, 2-octenyl succinic anhydride, and acetic anhydride.
5. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The preparation method of collagen comprises the following steps: adding water to gelatin to adjust the mass fraction of gelatin to 5%-8%, adjusting the pH of the system to 8-10, heating to 50-60°C, adding a gelatin modifier, maintaining the temperature at 50-60°C for reaction for 1-2h, dialyzing with deionized water, concentrating, and freeze-drying to obtain collagen.
6. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The alcoholysis degree of the PVA is ≥99%, the viscosity of the PVA aqueous solution with a PVA mass concentration of 4% is 24-32 cP, and the ash weight is <0.5%.
7. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: B1. After the montmorillonite is crushed and passed through a 200-400 mesh sieve, water is added to adjust the mass fraction of the montmorillonite to 3%-5%, the temperature is raised to 75-85°C and stirred evenly, a quaternary ammonium salt aqueous solution is added, and the mixture is reacted at 75-85°C for 8-10 hours, the mixture is separated and the liquid is removed, the solid is filtered 2-3 times, and vacuum dried at 60-70°C to obtain the quaternary ammonium salt modified montmorillonite; B2. After ultrasonically dispersing the quaternary ammonium salt modified montmorillonite in a 75%-85% ethanol aqueous solution for 1-3 hours, a coupling agent is added, and the pH value of the system is adjusted to 8-9. After reacting at 65-75°C for 2-4 hours, the mixture is cooled to room temperature, filtered and separated, and washed with deionized water until neutral. The modified montmorillonite is then vacuum dried at 60-70°C.
8. The oil-proof and tear-resistant paper bag for fried chicken according to claim 1, characterized in that: The method for preparing the oil-proof coating comprises the following steps: C1. Prepare modified starch emulsion, collagen aqueous solution, polysaccharide aqueous solution, sodium alginate aqueous solution, PVA aqueous solution and glycerol aqueous solution respectively for later use; C2. After stirring the modified starch emulsion and collagen aqueous solution at 65-75°C and 800-1000r / min for 20-30min, add the PVA aqueous solution, heat it to 85-95°C, stir it at 800-1000r / min for 1-2h, add the glycerol aqueous solution, keep stirring at 85-95°C and 800-1000r / min for 30-40min, cool it to 40-50°C, add the polysaccharide aqueous solution and the sodium alginate aqueous solution, continue stirring at 40-50°C and 800-1000r / min for 20-30min, add the modified montmorillonite, stir it at 40-50°C and 800-1000r / min for 20-30min, and obtain the product.
9. A method for preparing the oil-proof and tear-resistant paper bag for fried chicken according to any one of claims 1 to 8, characterized in that: The process comprises the following steps: fixing the paper on the coating machine, applying the oil-proof coating on the paper, and applying the coating amount of 2-4 g / m 2 , dry at 55-65℃ for 30-50min, and place at room temperature for 1-2 days to obtain.
10. Use of the oil-proof and tear-resistant paper bag for fried chicken according to any one of claims 1 to 8 in the field of food packaging.
Citation Information
Patent Citations
Cationoid esterified starch-grafted and modified acrylic resin paper waterproof agent and preparation method thereof
CN107383281A
Oil-proof paper and preparation method thereof
CN108999023A
Degradable environment-friendly antibacterial preservative film and preparation method thereof
CN112409735A